Sexual behavior and HBV infection among noninjecting cocaine users (NICUs) - Zocratto, Keli Bahia Felicíssimo (2010)
Fil: Zocratto, Keli Bahia Felicíssimo. School of Medicine, Federal University of Minas Gerais (UFMG), Belo Horizonte, Minas Gerais; Brasil.